Case report: Homozygous variants of NEB and KLHL40 in two Arab patients with nemaline myopathy - Skrypnyk, Cristina; Husain, Aseel Ahmed; Hassan, Hisham Y.; Ahmed, Jameel; Darwish, Abdulla; Almusalam, Latifa; Ben Khalaf, Noureddine; Al Qashar, Fahad (Frontiers in Genetics, 2023)
Objective: Nemaline myopathies are a heterogeneous group of congenital myopathies caused by mutations in different genes associated with the structural and functional proteins of thin muscular filaments. Most patients have congenital onset characterized by hypotonia, respiratory issues, and abnormal deep tendon reflexes, which is a phenotype encountered in the wide spectrum of neuromuscular disorders. Whole-exome sequencing (WES) contributes to a faster diagnosis and facilitates genetic counseling. Methods: Here, we report on two Arab patients from consanguineous families diagnosed with nemaline myopathy of different phenotype spectrum severities. Results: Clinical assessment and particular prenatal history raised a suspicion for neuromuscular disease. WES identified homozygous variants in NEB and KLHL40, respectively. Muscular biopsy and muscle magnetic resonance imaging studies linked the genetic testing results to the clinical phenotype. The novel variant in NEB gene resulted in a classical type of nemaline myopathy type 2, while the KLHL40 gene variant led to a severe phenotype of nemaline myopathy type 8. Both patients were identified as having other gene variants with an uncertain role in their complex phenotype. Conclusion: This study enriches the phenotypic spectrum of nemaline myopathy caused by NEB and KLHL40 variants and highlights the importance of detailed prenatal, neonatal, and infancy assessments of muscular weakness associated with complex systemic features. Variants of uncertain significance in genes associated with nemaline myopathy may correlate with the phenotype. Early and multidisciplinary interventions can improve the phenotype in patients with mild forms. WES is essential for clarifying complex clinical phenotypes encountered in patients from consanguineous families. Targeted carrier screening of extended family members enables more accurate genetic counseling and further genetic prevention.